Positive synchronisation of Mukhtalif al-Ḥadīth: an analysis of Ibn Qutaybah (d.276AH/894CE)’s methodology - Bahari, Che Amnah (2020)
The swell of censure in recent times on purportedly difficult and problematic aḥādīth of the Prophet has resurfaced for many detractors alleged that these narrations are illogical, irrational, impractical, or conflicting with Quranic teachings. Those narrations that have been tossed into the limelight for apparently problematic subject matter were systematically elaborated, discussed, and codified in detail by outstanding Muslim scholars of the past. Amongst them was Ibn Qutaybah al-Dīnawarī (d.276AH/894CE).